Edukasi Gizi Pekerja Mengenai Pemilihan Makanan di Aplikasi Pesan Antar Menggunakan Media Ebook “Boek-Krispy” - Hendrik Septiana; Ratih Kurniasari; Linda Riski Sefrina; Sabrina (Abdimas Universal, 2022)
In the era of adapting to new habits, online food delivery applications are increasingly being used, including workers. It is true that online food delivery applications can provide convenience, however, these activities actually provide greater opportunities for them to consume unhealthy foods because the average food is available is fast food. This activity aims to increase the knowledge of workers regarding the selection of healthy and balanced nutrition so that they can be wiser in choosing food in online food delivery applications so as to create optimal nutritional status. This activity is fully implemented online. participating were 65 office workers. The implementation of this activity includes filling out the pre test, providing nutrition education using the ebook "Boek-Krispy" media, and filling out the post test. The measuring instrument used is a knowledge questionnaire and statistical test (Wilcoxon). The result of this activity is that there is an increase in workers' knowledge about healthy food choices from 55.4% to 90.8% with an increase in the average score of 18%.